Use of Land Surface Temperature Estimation with Geographical Information Tools for Validation of Numerical Microclimate Studies at Urban Scale - Bustamante Mileyka (EDP Sciences, 2021)
For this study, different approaches found in the literature to obtain the Land Surface Temperature (LST) were evaluated through Geographic Information tools, to validate the temperature results obtained from dynamic simulations at urban scale with the Envi-met software. Here, the case study is an urban section of the Historic center of Panama City named Casco Antiguo. From the dynamic simulation results, the surface temperature was analyzed for March at 15:00. Concerning the results obtained for March, the Online Global Land Surface Temperature Estimation tool provided the best characteristics when validating the data obtained with Envi-met. It was found that the Landsat 7 images, applying the emissivity method ASTER and NDVI, provided data more stable and closer to the ones we wanted to validate.